INOVASI PEMBELAJARAN MELALUI BAI’AT DALAM MEMBENTUK KARAKTER KEDISIPLINAN PESERTA DIDIK - Agus Salim Mansyur; Nurti Budiyanti; Asep Abdul Aziz; Ari Prayoga (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
Education aims to develop the character of learners. To achieve this goal, teaching methods are necessary in education. So far, there has been no effective method applied in developing the character of learners. this research provides an overview of the level of discipline resulted from the ba’iat, as an effort to form the character of learners. It intends to find about how discipline is taught, implemented, and the supporting and inhibiting factors of the implementation of discipline as well as the impact of discipline teaching and implementation through bai’at in forming the character of learners. This research is based on a theoretical study which states that the implementation of discipline through bai’at can significantly improve discipline, and discipline is a key indicator of success in character formation. The success of learners in the formation of their character is, in some degree, influenced by the firmness of implementing the bai’at method. In this research, the author employed qualitative-descriptive method to find out how discipline is taught, how it is implemented, and what factors supportand inhibit the implementation and the teaching of discipline. The author also used quantitative method to determine the impact of teaching and the implementation of discipline through bai’at on the character formation of learners. The research was conducted at Pesantren Persatuan Islam 1 Bandung, and the respondents were 137 tenth grade Mualimien learners. The results of this study illustrate that the discipline teaching was in good category, with an average score of 3.562. The disciplinary implementation was also in good category, with an average score of 3.562. Then, the supporting and inhibiting factors were in the good category with an average score of 3.562. Finally, the impact of teaching and implementation of discipline through bai’at in the character formation of learners was in very good category, with an average score of 4.242. Thus, based on the results of the calculation, it is found that the teaching of discipline through bai'at has positive impact on the formation of the character of tenth grade Mualimien students of Pesantren Persatuan Islam 1 Bandung.